Analysis of the biocompatibility of various types of filling materials with the pulp-periodontal complex according to protein spectrum of gingival crevicular fluid - D. A. Ostanina; K. A. Archakov; Yu. A. Mitronin; O. A. Antonova; A. V. Mitronin (Эндодонтия Today, 2023)
Relevance. In practical dentistry, composite materials, cements, amalgam and metal-free ceramics are used to restore defects in hard tissues of teeth. Research data indicate that the type of filling material can affect the state of the pulpperiodontal complex of the tooth and lead to its degenerative changes.Aim. To study the state of the pulp-periodontal complex according to the protein spectrum of the gingival crevicular fluid of teeth filled with various types of restorative materials.Materials and methods. In the course of the study, the gingival crevicular fluid of the teeth was taken from 4 groups of patients using absorbent paper points of size 20 according to ISO: group 1 (control) – healthy teeth (n = 32); group 2 – composite materials (n = 12); group 3 – amalgam (n = 11); group 4 – metal-free ceramics E-max (n = 9). The activity of aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (AP) and lactate dehydrogenase (LDH) was studied in the obtained samples of gingival crevicular fluid using spectrophotometric analysis. Results. In the gingival fluid eluates, no statistically significant differences in the activity of ALT and AST enzymes were found between the studied groups. ALP activity in group 3 was 1.5 times higher than in groups 2, 4 and control, and the level of LDH in group 3 was 1.5 times higher than in groups 2, 4 and control.Conclusion. It was found that composite material and E-max metal-free ceramics have the best biocompatibility with teeth tissues, and the greatest changes in the protein spectrum of gingival fluid were detected in amalgam fillings.